The Intersection of Ideology, Subjectivity, and Social Psychology: A Psychoanalytic Approach - Velasquez, Nestor Raul Porras (Utan Kayu Publishing, 2024)
This study explores the role of ideology in social psychology and psychoanalysis by drawing on the theoretical approaches of key figures such as Martín-Baró, Moscovici, Lacan, and Žižek. The research highlights how ideology functions as a structure influencing human subjectivity and actions, particularly through the mechanism of fantasy as articulated in Lacanian theory. Ideology is not only seen as an explicit system of beliefs but also as an unconscious process that shapes identification and social interaction. Through in-depth analysis, this study demonstrates that fantasy plays a crucial role in reproducing ideological structures, thereby enabling the persistence of the existing social order. The study also expands our understanding of how gender and political ideologies are produced and reproduced in everyday life. By integrating psychoanalytic concepts and ideological analysis, this research offers a new perspective on understanding human subjectivity within a social context and proposes a more comprehensive theoretical framework for analyzing the relationship between social psychology and ideology. These findings are expected to contribute significantly to the existing literature and encourage further research in this field.